Commercially Available Essential Oil Formulas as Repellents Against the Stored-Product Pest Alphitobius diaperinus - Francikowski, Jacek (Insects, 2019)
The main aim of the presented paper is to assess the potential repellent effect of selected essential oils (EOs) against the lesser mealworm (Alphitobius diaperinus), which can cause economic losses in storage and in the poultry industry. Due to the development of pesticide resistance in A. diaperinus populations, as well as an attempt to limit extensive use of potentially harmful pesticides in food-related industries, there is a strong need for the development of alternative methods of dealing with A. diaperinus infestations. Because of their cost-effectiveness, availability and low vertebrate toxicity, EOs are promising agents in pest management. In the presented paper four off-the-shelf EOs: mint, vanilla, lemon and citronella (and mixtures of them) were tested as potential repellents. Moreover, a novel preference assay, providing an extended analysis of the preference and the locomotor response, was used. The most effective EOs were: citronella and lemon. EOs mixtures were generally more repellent than individual EOs, with the lemon and vanilla 1:1 mixture acting as the strongest repellent. A few of the tested EOs caused significant alterations to the locomotor activity, although no direct relation was observed. In conclusion, EOs can be potentially used as repellent agents in A. diaperinus management. Additionally, data on the locomotor activity may lead to designing better push-pull strategies in pest management.